The Semantic Analysis “Considering God’s Knowledge and Its Effects on Men’s Conducts” from the Perspective of the Quran Verses and Islamic Traditions - Abdul Hadi Masoodi; Abdul Hossein Kafi (آموزه‌های قرآنی, 2013)
From the point of the Quran verses and Islamic traditions, men’s considering God’s knowledge embodied (resulted in) many good effects. Among these consequences, moral influences of this subject seem more conspicuous. “considering God’s knowledge” causes the prevention of evils and so having virtues. The meaning of the prevention of evils is to stop sins, oppression, self-interest and so on. Some of the more general instances are mentioned by the Quran verses and Islamic traditions such as the prevention of jealousy, backbiting, accusation, betrayal, self-absorbed and hypocrisy. With respect to the Quran verses and Islamic traditions, the communication between key words of this semantic field is being all of these in men keeping away from sins and evils. There is a close relationship between this semantic field and some other semantic fields like the effects of considering God’s knowledge and the effects of remembrance (Dhik’r) of Allah is a partial order. (resemble each other in many points and denial iv a few aspects).